An improved fragmentation approach to sampled-data synchronization of chaotic Lur'e systems. (August 2018) - Park, JunMin; Lee, Seok Young; Park, PooGyeon
Abstract: This paper considers the sampled-data synchronization problem for two identical chaotic Lur'e systems. Under aperiodic samplings, the output of the chaotic Lur'e systems is available only at sampling instants. An improved fragmentation approach addresses a system description of the fragmented state located between the last sampling instant and present time. The sampled output of the fragmented state system is updated only at sampling instants, like the identical chaotic Lur'e systems. Thus, utilizing the additional information on the fragmented state system helps in handling the sampling interval. In the looped-functional framework, a sampled-data synchronization criterion is proposed for stability analysis and control synthesis about stabilization in terms of linear matrix inequalities. Simulation results show the effectiveness of the proposed criterion.